2018
DOI: 10.1139/cjz-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

Habitat overlap among bobcats (Lynx rufus), coyotes (Canis latrans), and Wild Turkeys (Meleagris gallopavo) in an agricultural landscape

Abstract: Wild Turkey (Meleagris gallopavo Linnaeus, 1758) populations have grown considerably in the Midwestern U.S. alongside mesocarnivores, such as coyotes (Canis latrans Say, 1823) and bobcats (Lynx rufus (Schreber, 1777)). However, few studies have assessed habitat overlap between mesocarnivores and turkeys with a goal to understand potential impacts of mesocarnivores on turkeys. We captured and radiomarked bobcats, coyotes, and Wild Turkey hens in southern Illinois during 2011–2013 in an agricultural landscape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Although contacts were rare, avoidance of areas of high predicted use by coyotes suggests male turkeys may avoid areas associated with increased coyote activity. However, we note that this avoidance could also be due to substantive differences in preference of landscape characteristics as suggested by Nielsen et al (2018). For example, coyotes use areas closer to shrubs and openings, whereas male turkeys showed strong selection for hardwoods and mostly selected areas away from open areas or showed no selection/avoidance.…”
Section: Discussionmentioning
confidence: 63%
“…Although contacts were rare, avoidance of areas of high predicted use by coyotes suggests male turkeys may avoid areas associated with increased coyote activity. However, we note that this avoidance could also be due to substantive differences in preference of landscape characteristics as suggested by Nielsen et al (2018). For example, coyotes use areas closer to shrubs and openings, whereas male turkeys showed strong selection for hardwoods and mostly selected areas away from open areas or showed no selection/avoidance.…”
Section: Discussionmentioning
confidence: 63%
“…In reality, a guild of multiple potential predators and a guild of multiple potential prey may exist and interact. For instance, coyotes prey on multiple small mammal species, which are also the prey of other coexisting mesocarnivores, which prey on wild turkeys (Nielsen et al, 2018). It is theoretically possible that the increased consumption of small mammals by coyotes would make the bobcat ( Lynx rufus ), another mesocarnivore, to kill more wild turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Bobcats tend to use larger home ranges in more fragmented and developed landscapes (Riley et al 2003, Tucker et al 2008) and lynx (Lynx lynx ) have been found to expand their home ranges in order to increase hunting efforts in areas with declining prey abundance (Schmidt 2008). Therefore, the fragmentated, patchy landscape and increased human modification in the central Illinois site could be leading to low-quality forage for bobcats, causing them to expand their home ranges to maintain access to necessary resources (Reding et al 2013, Nielsen et al 2017. Coyotes had larger home ranges than bobcats, but a large amount of variation was present within the coyote population (Gese et al 1988, Grinder andKrausman 2001).…”
Section: Predator Spatial Behavior and Response To Human Modificationmentioning
confidence: 99%